A novel brace with partial buckling restraint: Parametric studies and design method. (December 2021) - Zhou, Yiyi; Gao, Yuan; Wang, Chun-Lin; Chen, Lian-meng
Abstract: The yielding segment of the core plate is surrounded by the restraining member, making it difficult to directly inspect the buckling-restrained brace (BRB) after earthquakes. A new BRB, of which the core plate can be directly inspected without disassembling the BRB, is proposed. Only the edge of the core plate is restrained. The simulation models are verified based on previous tests, and the influence of the key parameters on the performance of the partially restrained buckling-restrained brace (PBRB) is compared based on 22 models. The design recommendation for PBRB is summarized. The main conclusions are as follows: The increase of the weak-axis gap d between the core plate and the restraining member can decrease the hysteretic energy-dissipation capacity and increase the weak-axis deformation of the core plate. The weak-axis deformation f of the core plate is selected as the performance evaluation criteria of PBRB, and it is recommended to be controlled within the core plate thickness t . When the unrestrained width-to-thickness ratio bu / t is constant, the change of the maximum weak-axis bulging deformation f max with the core plate thickness t is not obvious. To ensure that the new PBRB shows satisfied ductility after one strong earthquake and no damage after three strong earthquakes, the two performance levels and corresponding evaluation criteria are proposed, and the design recommendation for key parameters unrestrained width-to-thickness ratio ( bu / t ) and restrained width-to-thickness ( b-bu )/ t are given.